Relationships between state-level general population alcohol policies and birth outcomes: Results from 1972-2019 vital statistics. - Meenakshi S Subbaraman; Nancy F Berglas; William C Kerr; Sarah C M Roberts (PLoS ONE)
Background Research has found that policies that single out pregnant people's alcohol consumption are mostly ineffective. Identifying alternative approaches - for example, general population alcohol policies - that can reduce adverse effects of pregnant people's alcohol consumption is essential. Here, we examine how U.S. state-level alcohol policies regarding grocery store and gas station sales, Sunday sales, Blood Alcohol Concentration limits for driving, and government monopolies relate to birth outcomes. Methods Outcome data came from the 1972-2019 U.S. Vital Statistics System birth certificates (N = 160,538,939 live singleton births). Primary outcomes were low birthweight (<2,500 grams) and preterm birth (<37 weeks). Fully adjusted models included state and year fixed effects, state-specific time trends, and maternal- and state-level covariates with standard errors clustered by state. Results The only significant, robust associations between policies and outcomes were for government monopolies. In fully adjusted models, having a government monopoly on spirits or on both spirits and wine retail sales (vs. none) were each related to lower odds of low birthweight births (aOR=0.94, 95% CI: 0.93, 0.95; aOR=0.95, 95% CI: 0.92, 0.98 respectively). Having a government monopoly on spirits sales was also significantly related to lower odds of preterm births (aOR=0.97, 95% CI: 0.95, 1.00). Conclusions Government monopolies on spirits and wine relate to better birth outcomes. Findings underscore the importance of maintaining state government monopolies on spirits and wine as a strategy for protecting against adverse effects of pregnant people's drinking.